Role of electrolyte composition on the acid stability of mixed-metal oxygen evolution catalysts. Issue 72 (12th August 2020) - Li, Nancy; Keane, Thomas P.; Veroneau, Samuel S.; Nocera, Daniel G.
Abstract : Acid stability in catalysts that promote the oxygen evolution reaction (OER) involves an interplay between electrolyte and catalyst composition, both of which must be judiciously selected in order to promote activity and durability. Abstract : Acid stability in catalysts that promote the oxygen evolution reaction (OER) may be achieved through either the introduction of electrolyte-modulated self-healing processes, or the fixation of OER active sites within stable, conductive oxide matricies. By varying the nature of the electrolyte, pH, buffer concentration, and ionic strength, the contributions of these two effects may be deconvoluted. Furthermore, we find that the nature of the buffer is capable of engendering OER with exceptional acid stability at moderate overpotentials.